O processo de (trans)formação do leitor em ciumento de carteirinha, de Moacyr Scliar - Albuquerque, Everaldo Bezerra de (2015)
This work has with its main objective is evidence that the "citation" carries the persuasive function of an argument from authority, on the textual-rethoric of parameters disposal, which establish a thesis by means of an argument by reference. We treats about the ascertained whether the authority exercised by citation establishes communication with textual parts and vice versa, because if there is not this communication, the authority is undermined, not setting an argument in itself, but only by creating an allegory, without argumentative purposes, not to establish a consistent point of contact with the text. The citation is also recognized in rhetoric for argumentum ad verecundiam, and since a long time, refers to its persuasive function to justify given speeches. The methodology in this work is qualitative, without neglecting the contributions of quantitative research, because, at some point, is done recurrence some more accurate data. The survey corpus consists of eight (8) scientific papers, the result of 20% of a universe of 22 articles, which were produced during two semesters in the Postgraduate Studies in Language and Linguistics Program, at Federal University of Alagoas. To justify the theoretical basis of this study, we used in rhetoric: Aristotle (s / d 2005), Meyer (2007), Meyer (2008), Perelman (1996), Plantin (2008), Reboul (1998), Silveira (2005), Sousa (2001), Swales (1990), Toulmin (2006), among others. As for the textual studies, we have: Costa (2009), Dionysus and Hoffnagel (2012), Koch (2004), Marcuschi (2008), among others. The results point to an analysis of survey data, the scientific article genre, such as the presence of the argument from authority, the failure to establish the authority of argument in the fragment in which it operates citation, the identification of argument authority degrees, the latter being a contribution of this thesis, since it was not a theoretical record that measures the argument level. The relevance of this study is by recognizing the importance of rhetorical studies, associated with textual/discursive studies of genres, especially the academic genres.